Détection automatique de la présence d’anomalie sur une mammographie par réseau de neurones artificiels - Boukhobza Mohamed EL Habib et Mimi Malika (Courrier du savoir, 2012)
The breast cancer continues to be classified in the forefront of the public health problems. Proliferations of this disease push the researchers to develop techniques of assistance of diagnosis. The medical imagery constitutes animportant technique for assured a better quality the clinical diagnosis. Remain the problem of the quality of the interpretation of the medical image. The tracing routines organized of the breast cancer led to an increase amongst medical image interpreted and the needs for quality as regards public health make compulsory the recourse to the Assistance Systems Diagnosis (ASD) by computer. In this article we propose a system containing network of artificial neurons able to detect the presence or not anomaly on a mammography
Keywords: Mammographie ; Détection, Réseau de neurones artificiel ; Systèmes d’Aide au Diagnostic